Public health emergency operations center operations and coordination among Thailand, Cambodia, Lao PDR, and Malaysia during the COVID-19 pandemic - Royce Tsukayama; Natalie Wodniak; Soawapak Hinjoy; Charatdao Bunthi; Pasakorn Akarasewi; Walaiporn Jiaranairungroj; Wannaporn Pueyo; Wattana Masunglong; Pitchapa Kleblumjeak; John R. MacArthur; Emily Bloss (Taylor & Francis Group, 2023)
ABSTRACTPublic Health Emergency Operations Centers (PHEOCs) are the critical units to lead communications, information sharing, and resource mobilisation during national and international health emergencies, and are key components for maintaining global health security. This assessment sought to examine the coordination mechanisms between national and sub-national PHEOCs in Thailand, Cambodia, Lao People's Democratic Republic, and Malaysia (TCLM countries) during the COVID-19 pandemic. Information was collected on PHEOC structures, functions, and cross-border communications in three stages: a literature review of national PHEOC and emergency preparedness capacities; questionnaire responses from stakeholders to describe PHEOC activity at the national level; and meetings with emergency response staff in five border provinces of Thailand to assess communications between sub-national PHEOCs across country borders. The findings showed that each of the countries has demonstrated a commitment to strengthening their national PHEOCs and improving cross-border communication in the face of the COVID-19 pandemic. Strong existing relationships between TCLM countries assisted in activating a coordinated pandemic response, but gaps remain in efficient data sharing, workforce capacity, and the utilisation of consistent communication platforms among countries. Lessons learned from the pandemic can be used to further strengthen countries' preparedness for future health emergencies, in line with International Health Regulations (2005) and regional plans to build health security in the Southeast Asia region. This assessment provides TCLM countries with the opportunity to address weaknesses in national and international PHEOC capacities. It may be used alongside existing guidelines to prepare the region for a stronger response to future global and regional health emergencies.